Evangelizzazione e missionarietà - Filoni, Card. Fernando (Alpha Omega, 2020)
Summary: The Author stresses the need to put back at the center of the Church’s evangelizing and missionary identity. Evangelization is the task of all the baptized and involves giving an account of one’s faith; the missionary spirit adds a specific availability: that of proclaiming the Gospel wherever the name of Jesus has not been proclaimed. The author, therefore, reviews the challenges and ways of solving that the current situation of the world poses to the missionary spirit and explains its ongoing metamorphosis. If, in the past, the transmission of the faith was built around the figure of the missionary and the birth of the Church, today we feel the need for people and peoples to find themselves in the Church as at home. Hence the need to give life to a transmission of the Gospel that combines inculturation, interculturality and fraternity. Against all discouragement, it must be kept in mind that no transmission of the Gospel of Jesus would be possible if the Word and the Holy Spirit were not the first witnesses of the Gospel. Key words: Evangelization, being missionary, mission, inculturation, interculturality, fraternity, relativism, globalization, dialogue, transmission of the Gospel. Parole chiave: Evangelizzazione, missionarietà, missione, inculturazione, interculturalità fraternità, relativismo, globalizzazione, dialogo, trasmissione del Vangelo.